Deviant behaviors associated with aggressors and resilient subjects. A case-control study in Medellin, Colombia. 2003-2005 - Luis F. Duque; Joanne Klevens; Nilton E. Montoya (Universidad de Antioquia, 2007)
Concurrent risky or deviant behaviors of serious offenders, resilient men and community controls were estimated through a case-control study carried out in Medellin, Colombia between 2003 and 2005. Methodology: Cases: serious offenders (n=62), men involved in violent quarrels or brawls (n=81), and members of Autodefensas Unidas de Colombia -Colombian paramilitary army- (AUC), also known as paramilitaries (n=72) were compared to resilient men (n=59) and community controls (n=103). All were interviewed face to face in their communities. Cases were interviewed at the site, day and hour agreed with the group leader. Controls and resilient men were referred by respected and trusted persons of the community and interviewed in their own communities in a place chosen by them. Results: Antecedents of overt and covert aggression, deviant behaviors and oppositional behaviors, and substance abuse was higher among AUC members (paramilitaries), serious offenders and men involved in quarrels than among community controls and resilient men. Resilient men report a smaller number of concurrent deviant and risky behaviors compared to community controls. AUC members (paramilitaries) are not different from serious offenders in their reports of concurrent risky and deviant behaviors.